Clinical practice guidelines for percutaneous endoscopic gastrostomy - Chung Hyun Tae; Ju Yup Lee; Moon Kyung Joo; Chan Hyuk Park; Eun Jeong Gong; Cheol Min Shin; Hyun Lim; Hyuk Soon Choi; Miyoung Choi; Sang Hoon Kim; Chul-Hyun Lim; Jeong-Sik Byeon; et al. (Clinical Endoscopy, 2023)
With an aging population, the number of patients with difficulty in swallowing due to medical conditions is gradually increasing. In such cases, enteral nutrition is administered through a temporary nasogastric tube. However, the long-term use of a nasogastric tube leads to various complications and a decreased quality of life. Percutaneous endoscopic gastrostomy (PEG) is the percutaneous placement of a tube into the stomach that is aided endoscopically and may be an alternative to a nasogastric tube when enteral nutritional is required for four weeks or more. This paper is the first Korean clinical guideline for PEG developed jointly by the Korean College of Helicobacter and Upper Gastrointestinal Research and led by the Korean Society of Gastrointestinal Endoscopy. These guidelines aimed to provide physicians, including endoscopists, with the indications, use of prophylactic antibiotics, timing of enteric nutrition, tube placement methods, complications, replacement, and tube removal for PEG based on the currently available clinical evidence.